2022
DOI: 10.3389/fneur.2022.989280
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics next-generation sequencing for the diagnosis of central nervous system infection: A systematic review and meta-analysis

Abstract: ObjectiveIt is widely acknowledged that central nervous system (CNS) infection is a serious infectious disease accompanied by various complications. However, the accuracy of current detection methods is limited, leading to delayed diagnosis and treatment. In recent years, metagenomic next-generation sequencing (mNGS) has been increasingly adopted to improve the diagnostic yield. The present study sought to evaluate the value of mNGS in CNS infection diagnosis.MethodsFollowing the Preferred Reporting Items for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, the efficacy remains inconsistent, which warrants subsequent studies to further improve performance during clinical application. 49 , 52 In some cases, diagnostic sensitivity was increased by more than 18% to 20%, 49 , 51 without false positives, 51 independent of specimen type, 53 and without the need for viable or culturable pathogens. 35 However, mNGS can be less sensitive than polymerase chain reaction for detecting very low-level infections, 48 and as with other genomic methods, mNGS output still requires careful interpretation and substantial bioinformatics support.…”
Section: Resultsmentioning
confidence: 99%
“…However, the efficacy remains inconsistent, which warrants subsequent studies to further improve performance during clinical application. 49 , 52 In some cases, diagnostic sensitivity was increased by more than 18% to 20%, 49 , 51 without false positives, 51 independent of specimen type, 53 and without the need for viable or culturable pathogens. 35 However, mNGS can be less sensitive than polymerase chain reaction for detecting very low-level infections, 48 and as with other genomic methods, mNGS output still requires careful interpretation and substantial bioinformatics support.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a study on lung infection by Chen et al indicated a bacteria and fungi detection rate as high as 95% using mNGS, contrasting a mere 60% detection rate with traditional methods [ 15 ]. In addition, for central nervous system infections, mNGS diagnostic sensitivity and specificity reached 77% (95% CI, 70%–82%; I 2 = 39.69%) and 96% (95% CI, 93%–98%; I 2 = 72.07%), respectively [ 16 ]. Given its higher sensitivity and efficiency compared with standard tests, mNGS offers universal diagnosis of complex or severe pathogen infections.…”
mentioning
confidence: 99%